2015
DOI: 10.1093/mnras/stv490
|View full text |Cite
|
Sign up to set email alerts
|

A new spin on discs of satellite galaxies

Abstract: We investigate the angular and kinematic distributions of satellite galaxies around a large sample of bright isolated primaries in the spectroscopic and photometric catalogues of the Sloan Digital Sky Survey (SDSS). We detect significant anisotropy in the spatial distribution of satellites. To test whether this anisotropy could be related to the rotating discs of satellites recently found by Ibata et al. in a sample of SDSS galaxies, we repeat and extend their analysis. Ibata et al. found an excess of satellit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 51 publications
8
51
0
Order By: Relevance
“…Cautun et al (2015) studied the flattening of the satellite distribution around isolated central galaxies in the SDSS, as viewed on the plane of the sky, finding good agreement between data and cosmological simulations. Using a similar approach, Ibata et al (2015) claimed a higher degree of flattening in their data, but their conclusions may be affected by systematics (see Cautun et al 2015, for a discussion of this study). The expected signature of planar rotation has been investigated by considering the velocity correlation of satellite pairs observed on opposite sides of the host galaxy.…”
mentioning
confidence: 85%
“…Cautun et al (2015) studied the flattening of the satellite distribution around isolated central galaxies in the SDSS, as viewed on the plane of the sky, finding good agreement between data and cosmological simulations. Using a similar approach, Ibata et al (2015) claimed a higher degree of flattening in their data, but their conclusions may be affected by systematics (see Cautun et al 2015, for a discussion of this study). The expected signature of planar rotation has been investigated by considering the velocity correlation of satellite pairs observed on opposite sides of the host galaxy.…”
mentioning
confidence: 85%
“…While the velocity anti-correlation signal itself was confirmed by other studies, its interpretation as evidence for rotating planes of satellites has been challenged. 43,44 Two main concerns are that (1) the signal is less strong if satellite galaxies at larger radii from the hosts are included in the analysis, and that (2) no overabundance of velocity anti-correlation is found for larger opening angles. Both criticisms deviate from the originally intended analogy with the GPoA system.…”
Section: Statistical Approachesmentioning
confidence: 99%
“…Conn et al 2013;Shaya & Tully E-mail: shi.shao@durham.ac.uk 2013; Tully et al 2015), with many of their members showing correlated line-of-sight velocities that potentially a indicate co-rotating configuration (Ibata et al 2013;Müller et al 2018;Hodkinson & Scholtz 2019). Farther afield, Cautun et al (2015a) have shown that external galaxies also have anisotropic satellite distributions.…”
Section: Introductionmentioning
confidence: 99%
“…The plane of satellites most likely reflects the connection between a galaxy and its cosmic web. Multiple satellites are accreted along the same filament (Libeskind et al 2005;Buck et al 2015) which leads to a significant population of corotating satellites (Libeskind et al 2009;Lovell et al 2011;Cautun et al 2015a). Correlated satellite orbits can arise from the accretion of dwarf galaxy groups (e.g.…”
Section: Introductionmentioning
confidence: 99%